2010
DOI: 10.1307/mmj/1281531459
|View full text |Cite
|
Sign up to set email alerts
|

On the divisibility of Fermat quotients

Abstract: We show that for a prime p the smallest a with a p−1 ≡ 1 (mod p 2 ) does not exceed (log p) 463/252+o(1) which improves the previous bound O((log p) 2 ) obtained by H. W. Lenstra in 1979. We also show that for almost all primes p the bound can be improved as (log p) 5/3+o(1) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 17 publications
2
80
0
2
Order By: Relevance
“…It might be true that l p ≤ 3. Bourgain et al [42] have shown that l p ≤ log 463/252+o(1) p as p tends to infinity. As a consequence, they derive a stronger version of Lenstra's squarefree test.…”
Section: )mentioning
confidence: 99%
“…It might be true that l p ≤ 3. Bourgain et al [42] have shown that l p ≤ log 463/252+o(1) p as p tends to infinity. As a consequence, they derive a stronger version of Lenstra's squarefree test.…”
Section: )mentioning
confidence: 99%
“…Recently, some progress in estimating of exponential sums over "large" subgroups (but in Z/pZ not in Z/p 2 Z) such as (2) was attained (see [10]). So it is natural to try to use the approach from the paper to obtain some new upper bound for (1). Unfortunately, the methods from [10] cannot be applied directly in the case.…”
Section: Theorem 3 One Hasmentioning
confidence: 99%
“…Then |S(a)| ≪ p Heilbronn's exponential sum is connected (see e.g. [1], [2], [5], [6], [11], [12]) with so-called Fermat quotients defined as q(n) = n p−1 − 1 p , n = 0 (mod p) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite possible that a combination of [74,Proposition 3] with the results about nonvanishing Fermat quotient of [31,128] may lead to a result with a rather smooth s. Problem 63. Design and efficient algorithm, that for given x and y generates a "random" y-smooth number n ≤ x, that is, the output is always y-smooth and any y-smooth number appears with probability close to 1/ψ(x, y) where as usual ψ(x, y) = #{s ≤ x : s is y-smooth}.…”
Section: Commentsmentioning
confidence: 99%